Integrated Curriculum: Optimizing the Multiple Intelligences of Senior High School Students in Indonesia - Falaqi Muhamad Rizal; Yusuf Athayya Einosar; Husein, Muhammad Ghafiq; Susanto, Nabil Huga Arundaya; Nugroho, Arsya Sakha; Firdausy, Alif, Dzulfiqar Achmad; Abdurrahim, Istna Hasan (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: With the goal of maximizing students’ Multiple Intelligences (MI), this study aims to describe curricular integration in the senior high school context and explores how it is applied as the main curriculum strategy in senior high schools. Methodology: An international boarding school is the context of the case study methodology. Using a Triangulation method technique, direct observation, interviews, and documentation are all part of the data collection process. Reducing, organizing, and extrapolating conclusions from data with content analysis was performed. Findings: According to the research findings, the "Holistic and Balanced Education" curriculum is made up of four condensed components that are used to carry out curriculum integration. In order to improve students’ learning competencies, an interdisciplinary curriculum and the Contextual Teaching and Learning (CTL) methodology are used in every learning activity. Character development entails establishing the key qualities of RECODING (Religious, Caring, Open-minded, Inspiring). Class programs that focus on specialization help students develop their skills. An assessment is then carried out for every curricular element that has been put into practice.Implications/Novel Contribution: The study uniquely contribute towards bridging research gap of MI in curriculam and teching. All of these elements are intended to optimize students’ MI and fulfill the curriculum’s objective of generating graduates who are ethically superior, motivating leaders, and internationally minded, which makes this subject intriguing. To improve the curriculum and provide evaluative metrics targeted at attaining interdisciplinary insights, we advise teachers to receive further training and direction.